Families and work: revisiting barriers to employment - Bashir, Nadia; Crisp, Richard; Gore, Tony; Reeve, Kesia; Robinson, David (London, 2011)
"In recent years, considerable effort has been put into supporting parents to make the transition into work. The Department for Work and Pensions (DWP) commissioned the Centre for Regional Economic and Social Research (CRESR) at Sheffield Hallam University to undertake a study to explore whether these incentives were helping parents to overcome the barriers known to impede their engagement in the formal labour market. The research focused on two main tasks: